If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x+61)/7=4x+3
We move all terms to the left:
(3x+61)/7-(4x+3)=0
We get rid of parentheses
(3x+61)/7-4x-3=0
We multiply all the terms by the denominator
(3x+61)-4x*7-3*7=0
We add all the numbers together, and all the variables
(3x+61)-4x*7-21=0
Wy multiply elements
(3x+61)-28x-21=0
We get rid of parentheses
3x-28x+61-21=0
We add all the numbers together, and all the variables
-25x+40=0
We move all terms containing x to the left, all other terms to the right
-25x=-40
x=-40/-25
x=1+3/5
| 7(2l+8)=70 | | 4e-4=3.6 | | 12x+9-9=81-9 | | X+4x+4x+135+135=540 | | 11.3x-66=99 | | -13y=23 | | 6x–15x=-9x | | x+x+29=159 | | 29+4=x+7 | | 4x-16+25x+25=20x+30+15 | | 8(a+9)=120 | | x/12=6/24 | | 13x+9=(1+7x)=2 | | 29+x=x+7 | | 3(12-2y)-2y=8 | | 30+4y=14 | | -5*(u+2)=3*u-2 | | x-20=0.4x+5+0.25x | | 7÷x=2÷3 | | 25=a | | 2x-4=5(3x-2)-1 | | -14+2x=-3x+3 | | 25=a÷5 | | 4(u-3)=2u+6 | | 1÷3n=15 | | 5x+14=−2x−7 | | 2-x/6+x-3/3=3x+6/9 | | -6t+1=-11 | | c/6-20=16 | | 9z-7=3 | | 3/(2x+1)=-2/(x-5) | | 4x+11=-29x-6x |